(3GdLhgQI GdeYfhjI Ydi GdBLQhejIs - (3CHhGdMSf Rjf GdOjf Ydj Hf fGUQ GdOjf eMeO Hf eMeO Hf Nda Hf LHQjd Gdefhaj GdeUQj GdTGPdjs; (3Gdefhaj , Ydj Hf eMeO Hf eMeO Hf Nda GdeUQj GdTGPdj, CHh GdMSf,J (B939 (3g` s
(3ChdgG (B:s
(3CeG HYO, ajbhd Efg deG cGf ef CLd GdYdhe hCTQagG Yde GdYQHjI, EP Hg jage cdGe Gddg s
(3BNQgG (B:s
(3KGdKkG(B: (3hgh Cf Jchf GdEVGaI ajg abO JbOe aj GdeQahYGJ adjQGLY LejY Pdc Je gPG GdTQM s
(3GNJUQg GdeDda ef TQMg GdeWhd Ydi GdGLQhejIs
(3GdBLQhejI ebOeI aj GdfMh CdagG eMeO Hf BLQhe GdeJhai (B723 (3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdfMhs